Potassium sources in covering fertilization on cotton II - Nutritional status evaluation of crop - Echer, Fábio Rafael [UNESP]; Foloni, José Salvador Simoneti; Creste, José Eduardo (Universidade Estadual de Londrina, 2009)
A field experiment was conducted in Sapezal, Mato Grosso state, Brazil, in the 2007/2008 agricultural season, with the aim of determining the effect of potassium sources on cotton nutritional status. The treatments consisted of application in covering, via soil, at rate of 100 kg ha-1 of K 2O, in two split applications, with KCl, K2SO4, KNO3 and K2SO4.2MgSO4 sources. Nutrients concentration in leaf tissues at bloom stage was evaluated, being interpreted by the critical level and the DRIS methods. S content in cotton leaves and the S index was higher when used K2SO 4.2MgSO4 fertilizer. The Nutritional Balance Index (NBI) values were coherent with cotton yield, being the highest yields obtained with the smallest NBI in the covering fertilization with K 2SO4.2MgSO4.
Fontes de potássio na adubação de cobertura do algodoeiro II - Avaliação do estado nutricional da cultura
Keywords: Critic level; DRIS; Gossypium hirsutum L